2021
DOI: 10.3389/fmed.2021.622577
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in COVID-19: 90 Days of the Pandemic in a Brazilian Public Hospital

Abstract: Renal involvement is frequent in COVID-19 (4–37%). This study evaluated the incidence and risk factors of acute kidney injury (AKI) in hospitalized patients with COVID-19.Methodology: This study represents a prospective cohort in a public and tertiary university hospital in São Paulo, Brazil, during the first 90 days of the COVID-19 pandemic, with patients followed up until the clinical outcome (discharge or death).Results: There were 101 patients hospitalized with COVID-19, of which 51.9% were admitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
3
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 43 publications
8
44
3
12
Order By: Relevance
“…Here, we report a 37.6% AKI occurrence, consistent with 3 studies conducted in the USA and Brazil with 36.6%, 43%, and 50% AKI occurrence rates [ 6 , 11 , 17 ]. Nevertheless, this rate is higher than the largest meta-analysis performed to date by Fu et al [ 15 ], with the pooled incidence rate of 28.6% for AKI, reported in hospitalized COVID-19 patients from the USA and Europe.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here, we report a 37.6% AKI occurrence, consistent with 3 studies conducted in the USA and Brazil with 36.6%, 43%, and 50% AKI occurrence rates [ 6 , 11 , 17 ]. Nevertheless, this rate is higher than the largest meta-analysis performed to date by Fu et al [ 15 ], with the pooled incidence rate of 28.6% for AKI, reported in hospitalized COVID-19 patients from the USA and Europe.…”
Section: Discussionsupporting
confidence: 90%
“…Kidney involvement, including acute kidney injury (AKI), proteinuria, and hematuria, has been a recent finding among patients hospitalized with COVID-19 [ 2 , 3 , 4 ]. AKI is one of the most severe types of kidney involvement reported at various rates from 0.5% to as high as 50% in multiple studies in different countries [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], and is considered a prognostic factor impacting both severity and mortality [ 1 , 15 , 16 ]. Many pathophysiological pathways have been suggested for kidney abnormality in COVID-19 patients, including direct invasion and cytotoxic effect of the virus on kidneys leading to acute tubular necrosis supported by evidence of SARS-CoV-2 in kidney biopsy and urinary detection.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Newly published studies follow the same trend of increasing mortality with increasing AKI severity, indicating little respite despite advances in clinical management. 31 Individual studies vary considerably in the magnitude of the association (eg, 1.60 to 29.17 for severe AKI) and our estimates are consistent within these ranges. While the relative risks of death associated with AKI are consistent, it is important to note that the absolute risk of death in our study is high at almost 15% for those without AKI and over 50% for those with AKI, while existing literature notes absolute risk difference for AKI mortality to be 21.5% and relative risk at 3.63 (cumulative incidence of 29.6% in patients with AKI and 8.1% in non-AKI patients).…”
Section: Discussionsupporting
confidence: 74%
“…A Brazilian study was published recently and showed overall AKI incidence of 50%. Among ICU patients, AKI occurred in 77.3% and the mortality was 65.4% 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that COVID-19 patients who developed AKI had increased mortality risk [9][10][11][12][13][14] . A recent study of 5,449 individuals admitted to hospitals across New York, found that 35% of patients who developed AKI died, with an adjusted odds ratio (OR) of 9.6 12 .…”
Section: Introductionmentioning
confidence: 99%